Demographic profile of families and children in the Study to Explore Early Development (SEED): Case-control study of autism spectrum disorder. Issue 3 (July 2016) - DiGuiseppi, Carolyn G.; Daniels, Julie L.; Fallin, Daniele M.; Rosenberg, Steven A.; Schieve, Laura A.; Thomas, Kathleen C.; Windham, Gayle C.; Goss, Cynthia W.; Soke, Gnakub N.; Currie, Dustin W.; Singer, Alison B.; Lee, Li-Ching; et al.
Abstract: Background: The Study to Explore Early Development (SEED) is designed to enhance knowledge of autism spectrum disorder characteristics and etiologies. Objective: This paper describes the demographic profile of enrolled families and examines sociodemographic differences between children with autism spectrum disorder and children with other developmental problems or who are typically developing. Methods: This multi-site case-control study used health, education, and birth certificate records to identify and enroll children aged 2–5 years into one of three groups: 1) cases (children with autism spectrum disorder), 2) developmental delay or disorder controls, or 3) general population controls. Study group classification was based on sampling source, prior diagnoses, and study screening tests and developmental evaluations. The child's primary caregiver provided demographic characteristics through a telephone (or occasionally face-to-face) interview. Groups were compared using ANOVA, chi-squared test, or multinomial logistic regression as appropriate. Results: Of 2768 study children, sizeable proportions were born to mothers of non-White race (31.7%), Hispanic ethnicity (11.4%), and foreign birth (17.6%); 33.0% of households had incomes below the US median. The autism spectrum disorder and population control groups differed significantly on nearly all sociodemographic parameters. In contrast, the autism spectrum disorder and developmental delay or disorder groups had generally similar sociodemographic characteristics. Conclusions: SEED enrolled a sociodemographically diverse sample, which will allow further, in-depth exploration of sociodemographic differences between study groups and provide novel opportunities to explore sociodemographic influences on etiologic risk factor associations with autism spectrum disorder and phenotypic subtypes.